Environmental change and African societies - Haltermann, Ingo; Tischler, Julia, 1982- (Climate and culture (Leiden, Netherlands), 2020)
The volume Environmental Change and African Societies contributes to current debates on global climate change from the perspectives of the social sciences and the humanities. It charts past and present environmental change in different African settings and also discusses policies and scenarios for the future. The first section, "Ideas", enquires into local perceptions of the environment, followed by contributions on historical cases of environmental change and state regulation. The section "Present" addresses decision-making and agenda-setting processes related to current representations and/or predicted effects of climate change. The section "Prospects" is concerned with contemporary African megatrends. The authors move across different scales of investigation, from locally-grounded ethnographic analyses to discussions on continental trends and international policy. Contributors are: Daniel Callo-Concha, Joy Clancy, Manfred Denich, Sara de Wit, Ton Dietz, Irit Eguavoen, Ben Fanstone, Ingo Haltermann, Laura Jeffrey, Emmanuel Kreike, Vimbai Kwashirai, James C. McCann, Bertrand F. Nero, Jonas Ø. Nielsen, Erick G. Tambo, Julia Tischler.